Adaptive visual tracking via multiple appearance models and multiple linear searches - Nguyen, Tuan (2015)
This research is concerned with adaptive, probabilistic single target tracking algorithms. Though visual tracking methods have seen significant improvement, sustained ability to capture appearance changes and precisely locate the target during complex and unexpected motion remains an open problem. Three novel tracking mechanisms are proposed to address these challenges.